8. The Dramatic Literary Text as an Art Object in the Process of Teaching/Learning the French Language in the University Context - Gagim Ion; Chiriță Mariana (Sciendo, 2023)
The given article focuses on the study of the dramatic literary text as an art object used in the process of the teaching/learning French as a foreign language. The dramatic literary text, being one of the main elements of the dramatic art, which in turn is a syncretic one, requires an integrated approach in the interpretation process, both as a literary product and as a performance.